Bioinformatics and Microarray Technology - Kiran Mazumdar Shaw; SMH Qadri (New Delhi CBS, 2010)
This book have become major fields with hugely important application.
Protein Data Bank Sequence Alignment Biological Databases
Keywords: Protein Data Bank, Sequence Alignment, Biological Databases